Effect of Concurrent Chemo Radiation in the Treatment of Locally Advanced Carcinoma of Tongue - Mitra, Tapash; Uddin, Md Mokhles; Yousuff, Sajjad Mohammad; Awal, Mohammad Abdul; Chowdhury, Ali Asgar; Md Nizamuddin, - (Journal of Chittagong Medical College Teachers’ Association, 2012)
This quasi experimental study was conducted to observe the effects and toxicities of concurrent chemo radiation in locally advanced tongue cancer from January 2009 to December 2009 in the Radiotherapy Department of Chittagong Medical College Hospital. A total number of forty patients were purposively selected according to inclusion criteria. Among them, 30 patients presented with lesion in anterior two third & 10 patients in posterior one third. Thirty patients were male & ten were female. All of the patients having betel nut chewing habit & 90% were smoker & tobacco leaf chewer. The mean age of patient was 56.25 years. All patients received chemotherapy on D1, D8, D15, D22, D29, D36, D43 & 66 Gy external beam radiotherapy in 200 cGY/day in six and half weeks. Pretreatment status of mean size of primary lesion of anterior two third and posterior one third of tongue cancer patients significantly decreased in last follow up. Mean size of lymph nodes significantly decreased from pretreatment to last follow up in both anterior two third and posterior one third of tongue cancer patients. Over all response of patients treated with concurrent chemo radiation only three patients of anterior two third & one patient of posterior one third showed complete response followed by seventeen patients of anterior two third & five patients of posterior one third showed partial response. Response is better in stage III than stage IV patients in both anterior two third and posterior one third of tongue cancer. The common toxicities are mucositis, skin reaction, anemia & leucopenia in both anterior two third and posterior one third of tongue cancer patients. In the treatment of locally advanced carcinoma of tongue, coneurrent chemoradiation showed better symptom improvement, manageable toxicities. So, concurrent chemoradiation may be one of the treatment modality in locally advanced carcinoma of tongue patients. Period of study and number of patients were small. So, long term follow-up and large number of patients should be included to conduct more in-depth research and more specific comments. JCMCTA 2012; 23(1): 36-41